Correlation between extracurricular activities and academic performances among preclinical medical students in Udayana University, Bali, Indonesia - Muhammad Faisal Putro Utomo; Ida Ayu Dewi Dhyani; I Gusti Agung Ayu Andra Yusari; I Putu Hendri Aryadi; Ni Putu Diah Utami Darmayanti; I Gde Haryo Ganesha (Intisari Sains Medis, 2019)
Background: Medical students are required to develop ability and clinical skill to carry out the profession. Soft skill is also important to enhance the students’ performance when facing real-life situation in community. It can be developed through extracurricular activity which trains positive behavior, time management, and social aspect. This study was aimed to explore the correlation between extracurricular activities and academic performances among medical students in preclinical phase.Summary of Work: A cross-sectional study with total of 221 medical students of Udayana University in preclinical phase. Data were taken from data collecting by Student Executive Board for Credit Point of Participation which was the indicator of extracurricular activities and grouped into active and not active. Data were also taken from Academic Affair’s registered data (Grade Point Average (GPA) and gender). GPA was the indicator of academic performance and grouped into good and average. Data were analyzed using univariate and bivariate analysis (Chi Square Test with Cramer’s V).Summary of Results: From 221 medical students (males 43.9%; females 56.1%), 48% are active participants of extracurricular programs. Fifty-nine medical students had good GPA and 162 medical students had average GPA. The mean score of Credit Point of Participation are 116.545±65.79 and GPA is 3.3781±0.282 (out of possible 4). Our study showed a positive correlation between extracurricular activities and academic performance (r=0.2; p=0.003).Discussion & Conclusions: Medical students who are active participants in extracurricular programs have better academic performance than those who are passive. This finding may have similar result to some previous studies. Extracurricular activities lead to positive impact in academic achievement, because it can decrease any academic stress and tension, which lead into more productivity in their learning.